Pengaruh Status Gizi Dengan Konsentrasi Belajar Siswa di SD Negeri 2 Sumber Marga Telang - Dian Eka Anggreny; Meiranti (STIKes Payung Negeri Pekanbaru, 2023)
Banyuasin Regency ranks second with cases of wasting (8.79%), after North Musi Rawas (10.21%). Malnourishment in school-age children will result in children becoming weak, tired quickly and sickly so that children are often absent and have difficulty following and understanding lessons. The purpose of this study was to obtain information on the results of the effect of nutritional status on students' learning concentration. The research method used is descriptive qualitative. The informants in this study were 1 key informant PJOk teacher, 6 parents of student informants, 6 students and 1 class teacher support informant. Information collection tools guide in-depth interviews, observation, and recording devices. The results showed that there was an influence between nutritional status and student learning concentration, but there were factors that could influence the results of this study, namely socio-economic factors and breakfast